Analisis Keuntungan dan Nilai Tambah Usaha Keripik Singkong pada Usaha Home Industri â€œTiga Putra Sundaâ€ di Desa Sindangkasih Kecamatan Ranomeeto Barat Kabupaten Konawe Selatan - Wulandari, febri; Abdi, Abdi; Rosmawaty, Rosmawaty (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
This study aims to determine how much benefit and value added obtained from processing of cassava into cassava chips with two variants of taste (saltiness and flavor Balado) made the home business industry "Three Men Sundaâ€. The samples in this research is done intentionally on the consideration that the home business industry "Three Men Sunda" is the only business that perform processing cassava into cassava chips in the village of West Ranomeeto Sindangkasih District of South Konawe. Analysis of the data used in this research is by using the formula advantages and value added analysis method Hayami. The results showed that the cassava processing by the home business industry "Three Men Sunda" by using simple technology has created a profit of USDÂ  1,406,349.51 per the production process, and has also created an value of USD 16 990 kilograme for saltiness and Rp 16 270 per kilogram to taste Balado. The ratio of added value to each of these variants is 79.95% taste for saltiness and 75.67% for flavor Balado. This is due to the high value of the product, while the prices of raw and auxiliary materials tdak so great.